Belajar Do’a Harian Islam Pada Anak Usia 7-12 Tahun Di Kota Palembang Dengan Pendekatan Komunikasi Visual Board Game - Adelia, Amanda; Mubarat, Husni; Windu Viatra, Aji (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Prayer is required to be taught to children as early ac possible to form a more religious character. In Palembang, there are still few children who apply prayers in their daily lives, due to many factors. On of them is parents being busy with their work, then the kindergarten / TPA (Islamic school), and the lack of new and interesting learning media. The purpose of this design is to make children aware and encourage them to apply prayers in their daily lives and to create an engaging learning method. This design uses the design thingking method, which includes empathizing, defining, ideating, prototyping, and testing. Thee selected media include ( main media) a board game and an illustrated book, (pre media) x-banners, posters, digital posters, catalogs, and (follow-up media) beg tags, backpacks, pencils, erasers, rulers, pencil cases, quran pointers, long-sleeved t-shirts, tumblers, pins, sticker packs, and notebooks. It is hopen that this selection of media can serve as a tool to facilitate the teaching of daily Islamic prayers to children.